Asymmetric synthesis of the two enantiomers of β-phosphorus-containing α-amino acids via hydrophosphinylation and hydrophosphonylation of chiral Ni(ii)-complexes. Issue 10 (1st March 2021) - Tokairin, Yoshinori; Konno, Hiroyuki; Noireau, Angéline; West, Caroline; Moriwaki, Hiroki; Soloshonok, Vadim A.; Nicolas, Cyril; Gillaizeau, Isabelle
Abstract : A new approach for the synthesis of the two enantiomers of β-phosphorus-containing α-amino acids was developed via Michael addition of secondary phosphine oxides and dialkyl phosphites to chiral Ni(ii )-complexes of a dehydroalanine-Schiff base. Abstract : A new approach for the asymmetric synthesis of the two enantiomers of β-phosphorus-containing α-amino acids was developed via Michael addition of secondary phosphine oxides and dialkyl phosphites to chiral Ni(ii )-complexes of a dehydroalanine-Schiff base.